2020
DOI: 10.1371/journal.pone.0236400
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network models for identifying incident dementia using claims and EHR datasets

Abstract: This study investigates the use of deep learning methods to improve the accuracy of a predictive model for dementia, and compares the performance to a traditional machine learning model. With sufficient accuracy the model can be deployed as a first round screening tool for clinical follow-up including neurological examination, neuropsychological testing, imaging and recruitment to clinical trials. Seven cohorts with two years of data, three to eight years prior to index date, and an incident cohort were create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Deep learning can also help to identify features that are important for disease progression or serve as markers for clinical trials (Ithapu et al, 2015 ). In addition to harvesting brain imaging data [especially the multimodality imaging data from the public ADNI database ( http://adni.loni.usc.edu/ )], deep learning has been applied to biospecimens (Lee et al, 2019b ; Lin et al, 2020 ), electronic health records (Landi et al, 2020 ; Nori et al, 2020 ), speech (Lopez-de-Ipina et al, 2018 ), neuropsychological data (Choi et al, 2018 ; Kang et al, 2019 ), and a combination of MRI and neuropsychological data (Qiu et al, 2018 ; Duc et al, 2020 ). By contrast, few studies have applied deep learning to cognitive task data, which – by design – is supposed to be more sensitive to detect early and mild neurocognitive impairment (Locascio et al, 1995 ; Perry and Hodges, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning can also help to identify features that are important for disease progression or serve as markers for clinical trials (Ithapu et al, 2015 ). In addition to harvesting brain imaging data [especially the multimodality imaging data from the public ADNI database ( http://adni.loni.usc.edu/ )], deep learning has been applied to biospecimens (Lee et al, 2019b ; Lin et al, 2020 ), electronic health records (Landi et al, 2020 ; Nori et al, 2020 ), speech (Lopez-de-Ipina et al, 2018 ), neuropsychological data (Choi et al, 2018 ; Kang et al, 2019 ), and a combination of MRI and neuropsychological data (Qiu et al, 2018 ; Duc et al, 2020 ). By contrast, few studies have applied deep learning to cognitive task data, which – by design – is supposed to be more sensitive to detect early and mild neurocognitive impairment (Locascio et al, 1995 ; Perry and Hodges, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different outcomes were considered by different studies while incorporating ML or AI techniques. Major neurocognitive disorder, dementia, and Alzheimer's disease were the most common conditions among the articles included in our study and were reported in 11 studies ( 7 , 15 , 16 , 24 , 25 , 27 , 28 , 30 , 31 , 33 , 34 ). Among the other outcomes, a geriatric syndrome (falls, malnutrition, dementia, severe urinary control issues, absence of fecal control, visual impairment, walking difficulty, pressure ulcers, lack of social support, and weight loss) in 3 studies ( 18 , 21 , 22 ), delirium in 2 studies ( 20 , 32 ), mild cognitive impairment ( 33 ), cognitive disorder ( 26 ), multimorbidity pattern ( 23 ), mortality ( 29 ), hospital admission ( 17 ), and themes/topics mentioned in care providers' notes ( 19 ) were considered once.…”
Section: Resultsmentioning
confidence: 99%
“…Support vector machine ( 15 , 31 ) and topic modeling ( 19 , 24 ) were used by two studies each. Finally, lasso ( 33 ), naïve Bayes ( 28 ), multivariate information-based inductive causation (MIIC) network learning algorithm ( 26 ), fuzzy c-means cluster analysis ( 23 ), conditional restricted Boltzmann machine ( 27 ), WEKA ( 15 ), and gradient boosted trees ( 33 ) were applied by one study each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [62] researchers used longitudinal electronic health records from 2007 to 2017 including many features such as subject's age, background and clinical test results. Three models were trained on these data to predict MCI and AD within three to eight years using recurrent neural network (RNN), RNN with trained weights of another model, and a feed forward network.…”
Section: Large Scale Health Datamentioning
confidence: 99%